Correction to: Intensification of agriculture in southwestern Germany between the Bronze Age and Medieval period, based on archaeobotanical data from Baden-Württemberg - Tserendorj, Gegeensuvd; Marinova, Elena; Lechterbeck, Jutta; Behling, Hermann; Wick, Lucia; Fischer, Elske; Sillmann, Marion; Märkle, Tanja; Rösch, Manfred (Vegetation history and archaeobotany, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00334-021-00835-0